Analisis kesenjangan harapan dan kinerja lanskap jalan sebagai ruang terbuka publik saat car-free day di kawasan Renon, Denpasar - Tarigan, Yensa Margareth; Semarajaya, Cokorda Gede Alit; Adikampana, I Made (Jurnal Arsitektur Lansekap; Vol.5, No.1, April 2019DO - 10.24843/JAL.2019.v05.i01.p05, 2019)
The Gap Analysis of Expectancy and Performance of Streetscape as Public Open Space during Car Free Day in Renon Area, Denpasar. The numbers of open public space in Denpasar City have not been able to meet adequate ratios with population growth and urban development. To overcome this problem, one of the efforts that has been made by the government is to utilize the existing infrastructure into a temporary open public space which is the Car Free Day (CFD) Program. The shifting space utilization and the increase of activities on the streetscape will affect people perceptions who go there. This study aims to evaluate the Car Free Day program in Renon area base on the visitor satisfaction and streetscape performance. The analysis methods used are Costumer Satisfaction Index and Gap Analysis. The results of this study indicate that there are still disparities between the expectancy from the visitors with the streetscape performance. Car Free Day's Visitor satisfaction rate in Renon area is 78.4% in the range of 77% <X ? 80% which is "borderline". It means there are some unsatisfactory attributes and the performance needs to be improved.